Consequences of the rs6265 (Val66Met) polymorphism in the BDNF genein selected mental disorders and sport - Strońska, Aleksandra; Boroń, Agnieszka; Grzywacz, Anna (Current Problems of Psychiatry, 2022)
Introduction. Brain-derived neurotrophic factor (BDNF) is a polypeptide of 247 amino acid residues and is widely distributed throughout the central nervous system of the CNS. It plays an important role in the survival, differentiation, growth, and development of neurons in the central nervous system. The human BDNF gene is located on chromosome 11 in the p13-14 region and covers approximately 70 kb. The gene has a complex structure as it consists of 11 exons (I-IX, plus Vh and VIIIh) and nine functional promoters. BDNF expression in the brain is relatively low but it is found in most major regions of the brain.Material and methods. The gene encoding the brain-derived neurotrophic factor BDNF has many polymorphisms, but one of them mainly attracts the attention of researchers. This is a common, non-conservative polymorphism - rs6265 - a single nucleotide SNP polymorphism that results in an amino acid change – valine (Val) to methionine (Met) - at codon 66.Results. Polymorphism rs6265 is associated with many neuropsychiatric disorders, including depression or a higher risk of addiction, but it also determines other features, such as e.g. sports performance. Few studies are investigating the relationship between rs6265 polymorphism and predisposition to play sports.Conclusions. The results on the effect of rs6265 BDNF polymorphic variants on the risk of depression and addition are inconsistent, indicating a significant association in some studies and none in others. Therefore, more studies are needed to determine how rs6265 affects gene expression and function.